2020
DOI: 10.7717/peerj.9717
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the physical activity monitor for assessing energy expenditures in sedentary, regularly exercising, non-endurance athlete, and endurance athlete adults

Abstract: Background Inertial sensors, such as accelerometers, serve as convenient devices to predict the energy expenditures (EEs) during physical activities by a predictive equation. Although the accuracy of estimate EEs especially matter to athletes receive physical training, most EE predictive equations adopted in accelerometers are based on the general population, not athletes. This study included the heart rate reserve (HRR) as a compensatory parameter for physical intensity and derived new equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
0
3
0
5
Order By: Relevance
“…Such finding was concordant with previous studies that analyzed the consistency between self-reported levels of PA (similar to Bouchard) and single ACC ( 21 , 31 ). However, previous studies ( 32 34 ) showed high-percentage error and wide limits of agreement in EE estimation using Actigraph when compared with the golden standard tests, while only a few studies showed good validity in predicting EE in controlled treadmill activities or using light intensity stepping exercise ( 35 , 36 ). Therefore, it remains inconclusive to determine which method was better due to the lack of the gold standard method of EE estimation in the study.…”
Section: Discussionmentioning
confidence: 97%
“…Such finding was concordant with previous studies that analyzed the consistency between self-reported levels of PA (similar to Bouchard) and single ACC ( 21 , 31 ). However, previous studies ( 32 34 ) showed high-percentage error and wide limits of agreement in EE estimation using Actigraph when compared with the golden standard tests, while only a few studies showed good validity in predicting EE in controlled treadmill activities or using light intensity stepping exercise ( 35 , 36 ). Therefore, it remains inconclusive to determine which method was better due to the lack of the gold standard method of EE estimation in the study.…”
Section: Discussionmentioning
confidence: 97%
“…Окремим напрямів впровадження біомедичних технологій за авторством Chang, Hsu, Li, Tu, Jhang, Hsu, Huang, Ho, (2020) [6] є використання біомедичних тренажерів, які дозволяють вирішувати конкретні фізичні завдання і контролювати їх результати (рис. 2).…”
Section: рис 1 методика діагностики і контролю функціонального стану ...unclassified
“…• системна фізіологія -використання інженерних стратегій для аналізу експериментальних даних і формулюванні математичного опису фізіологічних подій для отримання комплексного та інтегрованого розуміння функції живих організмів та прогнозування фізіологічних реакцій при плануванні експериментів [6];…”
unclassified
“…Participants' average percentage of time per day on LPA, MVPA, and sedentary behavior were calculated based on the total wearing time and days and were then used in the data analysis. It was well-documented that ActiGraph accelerometer is a valid and reliable tool in measuring different intensi-ty levels of PA among adults (Chang et al, 2020;Clevenger et al, 2020;Montoye et al, 2017).…”
Section: Physical Activity and Sedentary Behaviormentioning
confidence: 99%